2011
DOI: 10.1111/j.1469-0691.2011.03459.x
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity and specificity of the C6-peptide ELISA on cerebrospinal fluid in Lyme neuroborreliosis patients

Abstract: Lyme neuroborreliosis (LNB) is a serious but treatable disease. The diagnosis of LNB poses a challenge to clinicians, and improved tests are needed. The C6-peptide ELISA is frequently used on serum but not on cerebrospinal fluid (CSF). Data on the sensitivity of the C6-peptide ELISA in CSF in patients suffering from LNB have been conflicting. Serum-CSF pairs from 59 LNB patients, 36 Lyme non-neuroborreliosis cases, 69 infectious meningitis/encephalitis controls and 74 neurological controls were tested in a C6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…For example, increased concentrations of CXCL13 (a chemoattractant for B cells) in CSF have been proposed as a biomarker for Lyme neuroborreliosis. Although European patients with Bannwarth syndrome typically have high levels of CXCL13 in CSF, which correlates with intrathecal antibody production against Lyme borrelia 191,192 , numerous other conditions can also cause increased levels of CXCL13, including neurosyphilis, HIV infection, CNS lymphoma and multiple sclerosis 192194 . Thus, for use as a diagnostic test for Lyme neuroborreliosis, the cut-off concentration of CXCL13 becomes crucially important and needs definition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased concentrations of CXCL13 (a chemoattractant for B cells) in CSF have been proposed as a biomarker for Lyme neuroborreliosis. Although European patients with Bannwarth syndrome typically have high levels of CXCL13 in CSF, which correlates with intrathecal antibody production against Lyme borrelia 191,192 , numerous other conditions can also cause increased levels of CXCL13, including neurosyphilis, HIV infection, CNS lymphoma and multiple sclerosis 192194 . Thus, for use as a diagnostic test for Lyme neuroborreliosis, the cut-off concentration of CXCL13 becomes crucially important and needs definition.…”
Section: Discussionmentioning
confidence: 99%
“…In retrospect, a brain biopsy might have delivered an earlier diagnosis, but the patient refused. There are scarce reports on seronegative patients who do indeed have intrathecal antibody production, so we cannot fully exclude the presence of Borrelia antibodies in this patient [ 12 , 13 ]. However, given the near-absence of B-cells in CSF, the lack of serum antibodies and the progressive meningo-encephalitic disease progress over months, we hypothesize that intrathecal antibodies were absent.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, our retrospective chart review of patients in a communitybased setting also found a majority (61 %) of those presenting with neurologic symptoms or arthritis were male (Aucott et al 2012). In the European setting, a male predominance for late-stage arthritis and neurologic complications has also been noted in clinic or referral-based patient samples (Renaud et al 2004;van Burgel et al 2011). For example, a recent analysis of chart reviews from a university medical center in Slovenia from 1990 to 2012 found that there was a male predominance among patients with Lyme arthritis and among those with neuroborreliosis .…”
Section: Late Lyme Diseasementioning
confidence: 98%